Healthcare utilization among patients with rheumatoid arthritis, with and without herpes zoster, a retrospective administrative data linked cohort study - Mohammad Movahedi; Angela Cesta; Xiuying Li; Mark Robert Tatangelo; Claire Bombardier (PLoS ONE, 2025)
Background Herpes zoster (HZ) infection is a significant concern among seniors and immunosuppressed patients including those with rheumatoid arthritis (RA). We aimed to compare healthcare utilization (HCU) and mortality in RA patients with and without HZ. Methods Patients from the Ontario Best Practices Research Initiative (OBRI) a clinical cohort (2008–2020) were linked to the Institute for Clinical Evaluative Sciences (ICES), a population health database. Each HZ patient was matched to four non-HZ patients based on sex, age, and HZ diagnosis date. The incidence of primary (HCU including hospitalization, Emergency Department (ED) visits, physician visits) and secondary (mortality and chronic clinical conditions) outcomes was calculated for each cohort, along with the impact of disease activity, patient-reported outcomes, and RA medication on these outcomes. Results The study included 269 RA patients with and 1072 without HZ. At index date (HZ diagnosis) patients with HZ were less likely to have private health insurance (45.7% vs. 56.5%) and more prone to use biologics (30.9% vs. 26.8%) and JAK inhibitors (3.7% vs. 2.6%). Hospitalization/ED visits and mortality were higher in HZ patients, but these differences were not statistically significant after adjusting for other factors. HZ patients had significantly more physician visits (adj IRR: 1.17; 95% CI: 1.03–1.33). Female sex and lower CDAI were associated with fewer physician visits. JAK inhibitor use was associated with increased mortality (adj HR: 4.73, 95% CI: 1.68, 13.4). Conclusion HCU was higher in RA patients with HZ, particularly in physician visits. Disease activity, patient reported outcomes and RA medication used did not have an impact on HCU and mortality.